Fluvial processes under late Pleni-Weichselian environmental conditions: a case study from the Warenka site in central Poland - Petera-Zganiacz, Joanna; Brzozowicz, Dorota; Pawłowski, Dominik; Kaczmarek, Paweł (Geologos, 2024)
Strong aggradational tendencies during the late Pleni-Weichselian have been noted in river valleys in central Europe. Thick series of mineral deposits were laid down, but also organic or mineral-organic horizons were formed under favourable conditions. The study area is located in the central section of the valley of the River Warta within an extraglacial area of the last glaciation. At the Warenka site alluvia, that attain thicknesses of 16 m, were analysed. Lithofacies analysis, OSL dating of mineral sediments and radiocarbon dating of organic and mineral-organic strata were performed. Organic and mineral-organic deposits were also subjected to pollen and Cladocera analyses. Together this set of analyses was used to determine fluvial processes and environmental conditions during the late Pleni-Weichselian. The results obtained allow the conclusion that these levels were deposited in the sedimentary environment of a low-energy, sand-bed braided river, which operated in the period from approximately 30 to 24 cal kBP – the late Pleni-Weichselian. During this time, there were periods when shallow water bodies were formed on the valley bottom, where deposition of organic material was possible. The presence of this type of sediment made it possible to reconstruct the vegetation cover; this had the character of a steppe-tundra, periodically shrubby steppe-tundra. Short-lived reservoirs were characterised by shallow-water settings with weakly developed vegetation and temporary influence of floodwaters as indicated by changes in cladoceran assemblages. Pollen spectra, low concentration of cladocerans, as well as the presence of the cold-tolerant Cladocera taxa are indicative of cold climatic conditions.